Premises and Motifs in Renaissance Thought and Literature - Patrides, C. A. (Book collections on Project MUSE., 1982)
In this work C. A. Patrides examines the Renaissance vision of a comely method and proportion" throughout the universe, whether in the vertical arrangement of the created order "from the Mushrome to the Angels" or the horizontal progress of history along a linear path from the Creation to the Last Judgment.Originally published in 1982.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.